Association between caring for grandchildren and feelings of loneliness, social isolation and social network size: a cross-sectional study of community dwelling adults in Germany. Issue 12 (17th December 2019) - Quirke, Eleanor; König, Hans-Helmut; Hajek, André
Abstract : Objective: The aim of this study was to examine whether there is an association between grandparental care and loneliness, social isolation and/or the size of an individual's social network among community-based adults aged ≥40 years. Methods: Cross-sectional data were drawn from a population-based sample of individuals aged ≥40 years living in the community in Germany. Loneliness was measured using a short version of the De Jong Gierveld Loneliness Scale. Social isolation was measured using a scale developed by Bude and Lantermann. The number of important people with whom respondents have regular contact (ie, social network size) was also used as an outcome variable. All respondents were asked whether they privately provide grandparent care (no/yes). Results: Linear regressions showed reduced loneliness (β=−0.06, p<0.01) and social isolation scores (β=−0.04, p<0.05) among those undertaking care of a grandchild. Regression analysis also showed an increased number of important people with whom individuals had regular contact among those who undertook care of a grandchild (β=1.02, p<0.001). Conclusion: Findings indicate a positive association between undertaking the care of a grandchild and the size of an individual's social network, and a negative association between grandchild care and self-rated scores of loneliness and social isolation. These findings build on existing research into the social and health implications of grandchild care among grandparents. Longitudinal studies are required to strengthen the understanding of this association.